Solution of Nonlinear Ordinary Delay Differential Equations Using Variational Approach - Abdullah, Zainab A (Al-Nahrain Journal of Science, 2012)
The main objective of this paper is to study the variational formulation of nonlinear problems, which may be given in general as a nonlinear ordinary differential equation, nonlinear partial differential equation, nonlinear integral equation , etc. and then introducing the variational formulation of nonlinear ordinary delay differential equations with its solution using the proposed approach given by Tonti.